Nanoemulsion Loaded with Clotrimazole Based on Rapeseed Oil for Potential Vaginal Application-Development, Initial Assessment, and Pilot Release Studies - Michał Smoleński; Susanne Muschert; Dorota Haznar-Garbacz; Katarzyna Małolepsza-Jarmołowska (MDPI AG, 2023)
Vaginal candidiasis (VC) is an emerging global hardly treated health issue affecting millions of women worldwide. In this study, the nanoemulsion consisting of clotrimazole (CLT), rapeseed oil, Pluronic F-68, Span 80, PEG 200, and lactic acid was prepared using high-speed and high-pressure homogenization. Yielded formulations were characterized by an average droplet size of 52-56 nm, homogenous size distribution by volume, and a polydispersity index (PDI) < 0.2. The osmolality of nanoemulsions (NEs) fulfilled the recommendations of the WHO advisory note. NEs were stable throughout 28 weeks of storage. The stationary and dynamic (USP apparatus IV) pilot study of the changes of free CLT over time for NEs, as well as market cream and CLT suspension as references, were conducted. Test results of the changes in the amount of free CLT released from the encapsulated form were not coherent; in the stationary method, NEs yielded up to 27% of the released CLT dose within 5 h, while in the USP apparatus IV method, NEs released up to 10% of the CLT dose. NEs are promising carriers for vaginal drug delivery in the treatment of VC; however, further development of the final dosage form and harmonized release or dissolution testing protocols are needed.